Acclimation and Characterization of Marine Cyanobacterial Strains Euryhalinema and Desertifilum for C-Phycocyanin Production - Khazi, Mahammed Ilyas; Li, Chenshuo; Liaqat, Fakhra; Malec, Przemyslaw; Li, Jian; Fu, Pengcheng (Frontiers in Bioengineering and Biotechnology, 2021)
This study involves evaluation of two cyanobacterial strains Euryhalinema and Desertiﬁlum isolated from mangrove pond in Haikou for their possible phycocyanin (C-PC) production. Maximal growth rate with highest chlorophyll and C-PC accumulation were observed at 28 °C and 60 μmol photons m−2 s−1 light intensity for Euryhalinema sp., while for Desertiﬁlum sp. at 32 °C and 80 μmol photons m−2 s−1. Nitrogen and iron concentrations trails revealed that, double strength concentration of sodium nitrate and ferric ammonium citrate in original BG11 media increased growth rate and accumulation of C-PC for both strains. Three different C-PC extraction methods were tested. The combined extraction protocol of Freeze-thaw and ultrasonication markedly increased the C-PC extraction efficiency and attained the food grade purity (A620/A280 ratio >0.7). Whereas, higher C-PC yield was found with Na-phosphate buffer. Furthermore, the clarified crude extract was used to purify C-PC by fractional ammonium sulfate ((NH₄)₂SO₄) precipitation, sephadex G-25 gel filtration chromatography and DEAE-sephadex ion exchange chromatography and attained the analytical grade purity (A620/A280 ratio >3.9). Taking together, both strains showed their potential to be domesticated for valuable phycocyanin production..